Carbon footprint of immunocastrated male fattening pigs compared to entire males, gilts, and surgically castrated males - Julia Gickel; Christian Visscher (Resources, Environment and Sustainability)
Efforts to minimize the environmental impact of livestock production are essential for sustainable agriculture. Immunocastration, using products like Improvac®, offers an alternative to surgical castration, enabling the physiological advantages of rearing entire male pigs while addressing issues such as boar taint and animal welfare. This review analyzes the effects of immunocastration on the performance and carbon footprint of fattening pigs compared to entire males, gilts, and surgically castrated males. Data from 39 trials reported in research articles were used to extract information on average daily gain (ADG), feed conversion ratio (FCR), and mortality. The means of these parameters were used to calculate the carbon footprint. Results showed that immunocastrated males had a higher mean ADG and a lower mean FCR compared to gilts and surgically castrated males, resulting in 7.1% and 6.8% lower carbon footprints, respectively. However, entire males had a slightly lower carbon footprint than immunocastrated males due to a more favorable FCR, although differences were not statistically significant. The findings underscore the ecological advantage of immunocastration over surgical castration, driven by improved feed efficiency and growth rates. From a sustainability perspective, boar fattening offers the lowest environmental impact, but practical challenges like boar taint and behavioral issues remain. If boar fattening is not feasible, immunocastration emerges as the preferable alternative to surgical castration, aligning with ecological and animal welfare goals. This review highlights the potential of immunocastration to balance productivity and sustainability in fattening pigs while addressing consumer and regulatory concerns.